Western Australia's Domestic Gas Reservation Policy: The Elemental Economics1. Issue 2 (13th February 2017) - Neill, Kelly
Abstract : Western Australia's domestic gas reservation policy nominally requires new gas export projects to supply the equivalent of 15 per cent of their exports to the domestic gas market. This export restriction suppresses the domestic price below the export netback price. A theoretical model shows that a binding reservation policy always causes a deadweight loss, and clarifies the source of this loss. Western Australia's reservation policy is estimated to cause losses with a present value of between $6.9 and $22.9 billion, depending on export netback prices.